Evaluation of Water Displacement Method in Estimating Mandibular Ramus Autograft Volume - BAYRAM, FERİT; AŞKIN EKİNCİ, SENEM; GÖÇMEN, GÖKHAN (My University, 2024)
Objective: This study aims to identify the most reliable method for measuring graft volumes comparable to those harvested from the ramus region using 3D-printed models. Methods: Using a cross-sectional design in an in vitro setting, CBCT images from 20 individuals who met the inclusion criteria for ramus grafting were examined. Volumetric evaluations were conducted on these images, and 3D-printed graft models were created. Two blinded raters assessed the graft volumes using the displacement method (with beakers of 10 cc, 25 cc, 50 cc capacity and a 100 cc biopsy cup) and the overflow liquid method (with beakers of 10 cc, 25 cc, and 50 cc capacity). The intraclass correlation coefficient and t tests were applied for statistical validation of intra- and inter-rater reliability. Results: High levels of both intra- and interrater reliability were observed, particularly for the 10 cc rise and overflow methods. These methods exhibited not only exceptionally high ICC values but also statistically meaningful p values. Furthermore, most of these methods strongly correlated and agreed with the CBCT measurements, except for the 50 cc overflow method, which showed significant divergence. Conclusion: The findings of this study validate the 10 cc beaker methods for reliable 3D printed ramus graft volume measurement and recommend a narrow-diameter syringe for optimal accuracy. These findings have crucial implications for both clinical practice and future research. Keywords: alveolar ride augmentation, three-dimensional image, organ size
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); alveolar ride augmentation; three-dimensional image; organ size